Nas dobras de correspondências e romances, o projeto poético machadiano - Balsini, Priscila Fernandes (2011)
Is there a dialogue between Machado de Assi's novels and letters? Do these letters reveal features of the author's poetic project? Considering the problematization of these questions, wich constitues de catalyst of this investigative process, we present the hypothesis that the letters of Machado de Assis are inscribed with the features of his poetic project. In the light of that, we began by the identification, in letters of the author, of revealing features of his poetic project and the verification of points of contact between his novels and letters. To this end, we took as the main corpus the book Correspondência de Machado de Assis com Joaquim Nabuco, José Veríssimo, Lúcio de Mendonça, Mário de Alencar e outros, seguida das respostas dos destinatários (1932), which brings the author's letters, collected by Fernando Nery. As a complementary corpus, we chose the novels mentioned in the epistles with a higher recurrence of Machado, Dom Casmurro and Memorial de Aires. As the research method adopted, we chose to follow two strands. The first guided by conceptual thinking, about epistolary genre and the poetic features, as conceived by studies by formalist and post-formalist schools. The second part was focused on the collection and review of letters and novels. The research led us to the conclusion that Machado's poetic project, masterminded and reflected both on his letters and novels, was planned and carried out meticulously and preciously by the author, who used masking games as a resource to convince, disguise, confuse and incite his audience - readers or correspondents. We consider this game as the very motor of Machado s writing, a device built in a strategic manner, in accordance with the observation of human reactions